Comparative lipid composition of heterotrophically and autotrophically grown Sulfolobus acidocaldarius. - Langworthy, T A (1977)
Complex lipids from the thermoacidophilic facultative autotroph Sulfolobus acidocaldarius, as well as a strictly autotrophic isolate, were compared between cells grown on yeast extract and elemental sulfur. Lipids from both organisms grown autotrophically were nearly identical. Each contained about 15% neutral lipids, 35% glycolipids, and 50% acidic lipids. Glycolipids and acidic lipids contained C40H82-76-derived glycerol ether residues. Major glycolipids included the glycerol ether analogues of glucosyl galactosyl diglyceride (5%) and glucosyl polyol diglyceride (75%). Acidic lipids were comprised mainly of the glycerol ether analogues of phosphatidyl inositol (7%), inositolphosphoryl glucosyl polyol diglyceride (72%), and a partially characterized sulfate- and phosphate-containing derivative of glucosyl polyol diglyceride (13%). The lipids from cells grown heterotrophically were similar to those from autotrophically grown cells, except that the partially characterized acidic lipid was absent. In addition, the two glycolipids as well as the respective inositolphosphoryl derivatives were each present in nearly equal proportions.